Effect of Baby Massage on Constipation in Babies Aged 6-12 Months - Andriyani, Asti; Agustina, Lusinta (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Constipation is a condition where feces (feces) are retained in the large intestine for a long time due to difficulty in expelling feces. One of the causes of constipation is the absence of peristaltic movements in the large intestine, which triggers irregular bowel movements and a feeling of discomfort in the stomach. Constipation can occur in babies who start receiving complementary foods from 6 months of age. The aim is to find out the effect of baby massage on the incidence of constipation in babies aged 6-12 months. Quasi experimental (pre experimental) research design with a pre test and post test design approach. The research was carried out in Tens Village, Trucuk Klaten District from February to October 2023. The population in this study were mothers who had babies aged 6-12 months. The sample in this study was 52 mothers who had babies aged 6-12 months with constipation. The treatment group consisted of 26 respondents and the control group consisted of 26 respondents. The sampling technique in this research is purposive sampling. The research results showed the effect of baby massage on the incidence of constipation in babies aged 6-12 months.